The Effect of Loan Portfolio Concentration Level on Financial Stability and Performance: A Comparatıve Analysis in Dual Banking System - Oğuzhan Ece; Bülent Diclehan Çadırcı (İktisat Politikası Araştırmaları Dergisi)
In this study, the effect of loan portfolio concentration on financial stability and performance was investigated in both conventional and Islamic banking systems. In the study examining the period of 2005-January and 2021-December, the long and short-term effects of credit portfolio concentration on financial stability and performance in the bilateral banking system were analyzed by cointegration tests. According to theempirical results, in which ARDL method for the conventional banking system and fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS) and canonical cointegrating regression (CCR) methods for the Islamic banking system were used, it has been found that the diversification of the loan portfolio reduces the bankruptcy risk in the conventional banking system in the long run and it has both positive and negative lagged effects in the short run. In the Islamic banking system, while there is no relationship between this diversification and financial stability in the long run, it has been concluded that it increases the risk of bankruptcy in the short run. When evaluated in terms of banking performance, it is seen that loan portfolio diversification does not cause a serious effect in the long or short term and does not cause differentiation within the bilateral banking system.